Penerapan Model Pembelajaran Flipped Classroom Untuk Meningkatkan Hasil Belajar di SMPN 36 Makassar - Irman, Dilla; Wahab, Abdul; Sumardin, Sumardin; Raehana, Syarifa; Nursetiawati, Nursetiawati (LP2M Universitas Islam Ahmad Dahlan, 2025)
The purpose of this study was to determine whether the Flipped Classroom learning model can improve student learning outcomes and whether it can be applied to the subject of Islamic Religious Education (PAI) in class IX.2 at SMPN 36 Makassar. A total of 32 students were involved in the Classroom Action Research (CAR) study, with 15 females and 17 males. This study used ten pre-test questions and five post-test questions, as well as observation sheets. Based on the results of the study, the application of the Flipped Classroom model was proven to improve student learning outcomes. The average learning completion in cycle I was 67.84% or 56.25%. After improvements in cycle II, completion increased to 87.5% with an average of 86.56%. These findings indicate that by implementing the Flipped Classroom learning approach in the PAI learning process in class IX.2 SMPN 36 Makassar, student learning outcomes increased significantly.